Research and development in the synthesis of cyanoacrylates - Gherardi, Stefano (Trinity College (Dublin, Ireland). School of Chemistry, 2010)
This dissertation is aimed at developing a new synthetic chemistry suitable for the selective production of highly reactive, high yield and purified electron deficient enes in bulk quantities.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.